TMIC-28. QUANTIFYING INTERSTITIAL FLUID FLOW IN GLIOBLASTOMA USING DYNAMIC CONTRAST ENHANCED MRI - Kingsmore, Kathryn (Neuro Oncol, 2017)
INTRODUCTION: Glioblastoma (GBM) is the most lethal brain tumor, characterized by high infiltration into the surrounding brain. This invasive nature makes GBM difficult to treat, rendering aggressive treatment strategies ineffective long-term with certain recurrence. Poor patient outcomes make GBM invasion research a priority and designing clinically relevant therapies to combat glioma requires understanding all mediators of GBM invasion. Interstitial fluid flow (IFF), an integral component of the tumor microenvironment, is one mediator of GBM invasion. IFF has been minimally studied in GBM and it is necessary to characterize IFF within the brain microenvironment and elucidate its effects on the surrounding tissue. METHODS: We inoculated male NOD-SCID mice with 15,000 glioblastoma stem cells (GSCs) (G2, G34, G528) 2mm lateral and 2mm posterior to bregma at a depth of 2.6mm. IFF pathways were monitored with T1-weighted dynamic contrast enhanced MRI (DCE-MRI) after intravenous injection of gadolinium or Fluorescein-conjugated gadolinium. Ten days after inoculation, intravenous Evans blue (50mg/kg in saline) was injected prior to intracardial perfusion. RESULTS: Using MRI techniques and multi-compartment models created in MATLAB, we computed preliminary IFF rates within the tumor and interstitium of our in vivo models. These fluid velocities ranged from 10µm/s to static. At the border between the tumor and healthy interstitium, average IFF rates were 1.4µm/s. Using MRI phantom systems we are validating our findings. Additionally, we are comparing flow pathways elucidated between Evans blue, the current standard molecule for identifying flow regions, and fluorescent gadolinium. CONCLUSION: We have shown that we can measure heterogeneous contrast dynamics reflecting IFF in and around brain tumors using DCE-MRI. Using our calculated in vivo flow rates to inform experiments, we will examine the flow response of these GSCs at different flow rates in vitro and expand our in vivo work to compare IFF in irradiated and untreated GBM models.